2007
DOI: 10.3892/or.17.4.841
|View full text |Cite
|
Sign up to set email alerts
|

Transketolase protein TKTL1 overexpression: A potential biomarker and therapeutic target in breast cancer

Abstract: Abstract. Malignant tumors degrade glucose to lactate even in the presence of oxygen via the pentose phosphate pathway (ppp). The non-oxidative part of the ppp is controlled by thiamine-dependant transketolase enzyme reactions. Overexpression of the transketolase-like-1-gene (TKTL1) in urothelial and colorectal cancer is associated with poor patient outcome. We analyzed the expression of the TKTL1 protein in a retrospective institution-based patient cohort with invasive breast cancer by immunohistochemical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 27 publications
2
54
1
1
Order By: Relevance
“…44 TKTL1 activity has been shown to supply ~85% of the C5-ribose sugars for nucleic acid synthesis, be overexpressed in a range of cancers including breast, and be essential for tumor cell proliferation. [45][46][47][48][49][50] Our results not only demonstrated an increase in SLC19A3 transporter expression but an increase in overall thiamine transport which could potentially be supporting the glycolytic phenotype of hypoxic cancer cells (Fig. 3).…”
Section: Discussionmentioning
confidence: 90%
“…44 TKTL1 activity has been shown to supply ~85% of the C5-ribose sugars for nucleic acid synthesis, be overexpressed in a range of cancers including breast, and be essential for tumor cell proliferation. [45][46][47][48][49][50] Our results not only demonstrated an increase in SLC19A3 transporter expression but an increase in overall thiamine transport which could potentially be supporting the glycolytic phenotype of hypoxic cancer cells (Fig. 3).…”
Section: Discussionmentioning
confidence: 90%
“…Important functions of TKTL1 in cancer biology have been proposed based on different observations. First, TKTL1 was shown to be expressed in a variety of tumor cells including glioma (37,38,57,58) and to be associated with malignant grade, presence of metastasis, and prognosis (57, 59, 60). Second, as putative mechanisms for these associations, TKTL1 has been demonstrated to increase glycolysis and hypoxia-inducible factor-1␣ (HIF-1␣) expression, proliferation (61,62), the generation of NADPH, and resistance toward ROS (40).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe a mechanism implicating TIGAR as a regulator of redox metabolism under hypoxic conditions and an activator of the mitochondrial respiratory chain in the oxygenated tumor fraction. Because (i) TIGAR exhibits an antioxidative function through the PPP (16,17), (ii) the PPP plays an important role in cancer (33)(34)(35)(36), and (iii) transketolase-like 1 (TKTL1), an isoenzyme of the transketolase, has been found to be overexpressed in different tumor types (18,(37)(38)(39) and was suggested to be important for PPP function and protection of tumor cells against oxidative stress (40), we also assessed a possible link between TIGAR and TKTL1.…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that the transketolase isoform transketolase-like protein1 (TKTL1), a key enzyme of the pentosephosphate pathway, is significantly overexpressed in human tumors, and TKTL1 expression correlates with poor patient outcome and more aggressive tumor progression (112). Genetic and pharmacological target validation confirms TKTL1 expression as an important factor in driving tumor cell growth and increasing tumor tolerance to oxidative stress (399).…”
Section: Oxythiaminementioning
confidence: 99%